2023
DOI: 10.1055/a-2061-7129
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic Acid: Signaling Pathways in Aging

Deepa Neopane,
Vaseem Ahamad Ansari,
Aditya Singh

Abstract: The need for clinical remedies to the multiple age-related deficiencies in skin function brought on by extrinsic and intrinsic causes is increased by these demographic changes. Reactive oxygen species (ROS), mitochondrial deoxyribonucleic acid (mtDNA) mutations, telomere shortening, as well as other factors, contribute to the aging of the skin. In this overview, the issue of human skin aging is introduced, along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In this study, we isolated and identified 15 phytochemicals, including a new oleanane-type triterpenoid saponin, 3-O-β-D-glucopyranosyl-oleanolic acid 28-O-β-D-glucuronopyranoside, in a methanolic extract of N. peltata roots and evaluated their protective effects on UVB-induced cellular injuries in HaCaT cells. Of these 15 compounds, α-spinasterol, ferulic acid, CQA, and TCQA markedly enhanced Nrf2-ARE luciferase activity; the antioxidant effects of α-spinasterol, ferulic acid, and CQA have been previously reported [43][44][45]. Therefore, we conducted further experiments on TCQA.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this study, we isolated and identified 15 phytochemicals, including a new oleanane-type triterpenoid saponin, 3-O-β-D-glucopyranosyl-oleanolic acid 28-O-β-D-glucuronopyranoside, in a methanolic extract of N. peltata roots and evaluated their protective effects on UVB-induced cellular injuries in HaCaT cells. Of these 15 compounds, α-spinasterol, ferulic acid, CQA, and TCQA markedly enhanced Nrf2-ARE luciferase activity; the antioxidant effects of α-spinasterol, ferulic acid, and CQA have been previously reported [43][44][45]. Therefore, we conducted further experiments on TCQA.…”
Section: Discussionmentioning
confidence: 91%
“…Regarding activation of the Nrf2-ARE pathway, compounds 1 (125%), 8 (138%), 10 (119%), and 15 (127%) significantly increased Nrf2-ARE luciferase activity compared to the untreated control (CON) group (100%). Out of the four, compounds 1, 8, and 10 have already been reported to have potential use as skin anti-aging treatments due to their ability to activate Nrf2 [43][44][45]. TCQA (15) treatment of Nrf2-ARE reporter HaCaT cells resulted in a significant concentration-dependent increase in Nrf2 activity, that is, it enhanced activity by 25% at 5 µM, 35% at 10 µM, and 54% at 20 µM, compared to the CON group (Figure 3B).…”
Section: Effects Of Compounds Isolated From N Peltata On Nrf2-are Luc...mentioning
confidence: 99%
“…In the case of resveratrol, the literature reports [156][157][158][159][160] different coordination complexes with Mn 2+ , Cu 2+ , Al 3+ , Zn 2+ , Fe 2+ , Ca 2+ or Mg 2+ . For ferulic acid, metal coordination complexes with Co 2+ , Ni 2+ , Cu 2+ , Zn 2+ , Mn 2+ , Mg 2+ , Fe 2+ , Fe 3+ and Na + are found [161][162][163][164][165][166][167][168][169][170]. For linoleic acid, metal complexes with Fe 2+ , Fe 3+ , Cu 2+ and Pt 2+ are described [171][172][173].…”
Section: Discussing Unexpected Dose-response Curves In Natural Bioact...mentioning
confidence: 93%
“…It mainly prevents the occurrence of oxidative stress by scavenging excessive intracellular ROS [ 25 ]. In addition, FA has been shown to have antiaging effects [ 26 ]. Since aging is often accompanied by oxidative stress [ 10 ], we hypothesized that FA can delay oocyte aging and improve oocyte quality by resisting oxidative stress.…”
Section: Introductionmentioning
confidence: 99%